PATTERN OF CUTANEOUS WOUND HEALING IN A ~IVE l~ISH CLARIAS BATRACHUS (L.) (CLARIIDAE, PISCES.) - DUTTA, M.; RAJ, A. K. (Journal of Indian Fisheries Association, 2015)
Incisional wounds of the same lengih and depth. were made on sldnbetween dorsal fin and the lateral line canal of Clarias batrachus andthe pattern of wound closure has been studied histologically. Followinginfliction, a marked change in the colour of the skin surrounding thewound was observed which lasted for about 30 h and. restoredthereafter. Mucus and blood cells plugged the wound gap shortly afterinfliction. The . epidenuis surrounding the wound was Â·found to bedetached from the basement membrane. !\lass movement of epidermalcells was observed from both side of the wound gap. The epidermalcells at the margin of the wound became hypertrophized. The epidernlisbeca.Ine normal by 32 days. The dealing of subepidermal tissue indicateddegenerative and Â·regenerative changes of muscle fibres. The mucusand blood cells were accumulated in the wound gap and later fineblood vessels. were forxned. Gradually granulation tissue was formedand fibroblasts and myoblasts appeared. Myoblast differentiated intomuscle bundles. The epidermal repair was completed within 85 days.